Implementation of MAKOC cyclic plasticity model with memory. (November 2017) - Halama, Radim; Markopoulos, Alexandros; Jančo, Roland; Bartecký, Matěj
Highlights: Limitations of the cyclic plasticity models available in FE codes are discussed. Prediction abilities of the MAKOC model are shown in tests realized on AA2124T851. Implementation of the robust cyclic plasticity model MAKOC is described in detail. The used return mapping algorithm can be applied to any mixed hardening model. The new numerical tangent modulus ensures parabolic convergence of the N-R method. Abstract: This paper deals with the description of implementation of the advanced cyclic plasticity model called MAKOC, which is based on the AbdelKarim–Ohno kinematic hardening rule, the isotropic hardening rule of Calloch and a memory surface introduced in a stress space in accordance with the Jiang-Sehitoglu concept. The capabilities of the MAKOC model are compared with the Chaboche model included in some FE codes. Cyclic plasticity models commonly included in commercial FE software cannot accurately describe the behavior of the material, especially in the case of additional hardening caused by non-proportional loading of the material. This fact is presented on the experimental data set of aluminum alloy 2124T851. Steady state material behavior is studied with regard to the subsequent application in computational fatigue analysis. The cyclic plasticity model developed was implemented into the FE code ANSYS 15.0 using Fortran subroutines for 1D, 2D as well as 3D elements. The integration scheme is described in detail including the method of implementing the model and determining an error map for the proposed MAKOC and Chaboche models. The numerical tangent modulus is proposed to ensure parabolic convergence of the Newton-Raphson method for the MAKOC model. An axisymmetric analysis of 3D Hertz problem was performed to show convergence in the local as well as global iterations.